Analisis Tingkat Kepuasan Pasien BPJS Unit Rawat Inap dengan Metode IPA di Rumah Sakit Baladhika Husada Jember Tahun 2019 - Mitha Amelia Rahmawati; Atma Deharja (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Inpatient services at Baladhika Husada Hospital in Jember still have problem to provide satisfaction to patientssuch as nurses not responsive and less friendly, room cleanliness is not maintained, electricity is oftenextinguished and air conditioners are not lit, toilet cleanliness is not maintained, the room is cramped andtemperature over the standard, inpatient BPJS registration process are complicated and parking space can’taccommodate. The purpose of this study was to determine the level of patient satisfaction of inpatient BPJSunits by the IPA method. Type of the research is quantitative research with descriptive techniques analysis.The IPA analysis method to measure the level of performance and importance based on quality, delivery,security, and morals by identifying the value of the gap and depicted in the Cartesian diagram. The level ofstatisfaction of inpatients based on the IPA method is known that the results of the analysis of the cartesiandiagra m illustrating four quadrans that top priority, maintained, low priority, and considered excessive. Theresults of the gap value based on quality, conductor, security, and morals are <1, but based on security thereis one attribute that has a gap >1. The main improvement efforts for brainstorming results are monitoring theperformance of cleaning services and conducting public speaking training for officers to improvecommunication